2019
DOI: 10.23910/ijbsm/2019.10.3.1976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Regulators on Yield and Quality of Tomato (Solanum lycopersicum L.) under Mid-hill Conditions of Himachal Pradesh

Abstract: Tomato (Solanum lycopersicum L.) member of family solanaceae is the world's most popular vegetable crop due to its wider adaptability to various agroclimatic conditions and multifarous uses. Plant growth regulators play an important role in increasing the growth, yield as well as quality of the produce if applied in suitable forms and at appropriate concentrations. Field experiments were conducted for two consecutive years during 2014 and 2015 to study the effect of plant growth regulators on tomato cultivar S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Added dose of nutrients increased the vigour of plants, assimilating area, and size of fruit, thereby resulting in higher T.S.S. These results are in close conformity with the findings of Ahmadi and Majidi [8]; Farooq et al [4]; Kumar et al, [5]; Islam et al [9], Ansary et al, [10]; Alam et al [6] and Mishra et al, [7] in tomato [11][12][13].…”
Section: Quality Parameter Tss [°Brix] Ascorbic Acid Content (Mg/100g...supporting
confidence: 88%
See 1 more Smart Citation
“…Added dose of nutrients increased the vigour of plants, assimilating area, and size of fruit, thereby resulting in higher T.S.S. These results are in close conformity with the findings of Ahmadi and Majidi [8]; Farooq et al [4]; Kumar et al, [5]; Islam et al [9], Ansary et al, [10]; Alam et al [6] and Mishra et al, [7] in tomato [11][12][13].…”
Section: Quality Parameter Tss [°Brix] Ascorbic Acid Content (Mg/100g...supporting
confidence: 88%
“…Integration of nutrients favoured vigorous growth and synthesized more of these hormones in plants, which might have helped the translocation as well as more quantity of available boron through the xylem vessels and their accumulation in the axillary buds that would have favoured the plant to enter the fruiting phase". Similar results have also been reported by Ahmadi and Majidi [8]; Farooq et al [4]; Kumar et al, [5]; Islam et al [9], Ansary et al, [10]; Alam et al [6] and Mishra et al, [7] in tomato.…”
Section: Number Of Flower Clusters Per Plant Number Of Fruits Per Clu...supporting
confidence: 87%
“…The findings we obtained are consistent with the findings of Long and Peng (2023), who reported that the combined application of N and B fertilizers has been shown to significantly increase crop yields. According to Sharma et al (2016), using lime together with 100% NPK increased garden pea yields above using NPK alone. The pH of the soil may have increased due to the use of lime in the lines, which may have decreased P and B fixation and increasing their availability in the acidic soil.…”
Section: Resultsmentioning
confidence: 99%
“…The perusal of data revealed that the effect of plant growth regulators on survival percentage of transplanted plants was found significant [3][4][5][6].…”
Section: Survival Percentagementioning
confidence: 99%